Respostas

A melhor resposta!
2014-07-19T13:32:30-03:00
Seria substituir o valor indicado na igualdade pelo "F(x)" nas equações

O primeiro seria assim:

F(x) = x       F(x)=2x          F(x)=-x               F(x)=x+1
F(x)=x.x      F(x)=x.2x        F(x)=x.(-x)          F(x)=x.(2x+1)           
F(x)=x²        F(x)=2x²         F(x)=-x²              F(x)=2x²+x  
                                                                         
                                     
2 5 2
2014-07-19T13:35:48-03:00
Y=X    X= 0

Y= 2X   2X = 0  X= 0/2  =0

Y = -X  -X = 0     X=0

Y= X + 1     X+1 = 0    X = -1

1 5 1